Decursin inhibits the growth of HeLa cervical cancer cells through PI3K/Akt signaling. Issue 6 (3rd June 2021) - Zhu, Meng-Lian; Li, Jian-Chun; Wang, Lu; Zhong, Xia; Zhang, Yu-Wei; Tan, Rui-Zhi; Wang, Hong-Lian; Fan, Jun-Ming; Wang, Li
Abstract: Decursin, a coumarin compound isolated from Angelica gigas has been shown to possess multiple anti-tumor activities. But it's still little known about the effects associated with cervical cancer. To explore the anti-tumor role of decursin and gain insights into its underlying mechanisms, we analyzed proliferation in parallel with apoptosis and migration in HeLa cells. Our findings implied that decursin can provoke apoptosis, and inhibit cell proliferation, migration in HeLa cells. More importantly, decursin also inhibited the tumor growth in vivo . The mechanisms may be associated with the regulation of Akt activation, with implications for novel therapeutic strategies on cervical cancer.